Technologies Utilization for Education Strategic Management in Social Distancing Era: A Literature Review - Theofilus Yoel Lufung (Budapest International Research and Critics University, 2022)
The background of this research is widespread in Covid-19 in Indonesia and takes many casualties. One of the government's efforts to reduce the spread of the virus is to create policies for students and students throughout Indonesia to study at home. To keep the material delivered and the learning process is not interrupted by the condition, distance learning is carried out through online learning. This research aims to find out the extent to which the application of online learning impacts the independence of student learning during the implementation distance learning. This article uses a qualitative approach in the form of literature. Sources of research data are 41 literature sourced from scientific articles journals about online learning during the COVID-19 period. Data analysis was carried out using the Microsoft Excel application. The results of data analysis of 41 articles obtained 39% for journals which stated that online learning had a negative impact and 61% for a positive impact. Therefore, online learning is feasible, but not by giving very many assignments with short collections, it can be replaced with joint discussions because it can support learning effectiveness and focus on learning. The use of learning media technology in the era of social distancing mostly uses whatsapp and zoom meetings.